2019
DOI: 10.1111/acfi.12522
|View full text |Cite
|
Sign up to set email alerts
|

Why is trait scepticism not consistently reflected in state scepticism? An exploratory study into the role of aesthetic engagement

Abstract: Where an auditor's sceptical disposition (trait scepticism) is directed toward non‐diagnostic information, there is a risk that a sceptical consideration of diagnostic information could be diluted. This may be one reason why trait scepticism is not consistently reflected in sceptical judgments and actions (state scepticism). We develop a scale to measure an individual's predisposition toward engaging with visual elements of the environment (aesthetic engagement) and test, in two experiments employing students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…In this case the focus in developing the aesthetic engagement scale was on traits, rather than states or conditions, where the underlying trait tendency to engage with aesthetically appealing elements of the environment, rather than behavior, feelings, or thoughts observed in a particular setting. This research also makes an important contribution to understanding how sceptical traits influence the level of skepticism reflected in audit judgements and is an initial stage leading to an expansion of focus in this regard to include other personality traits (Khan, 2019).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…In this case the focus in developing the aesthetic engagement scale was on traits, rather than states or conditions, where the underlying trait tendency to engage with aesthetically appealing elements of the environment, rather than behavior, feelings, or thoughts observed in a particular setting. This research also makes an important contribution to understanding how sceptical traits influence the level of skepticism reflected in audit judgements and is an initial stage leading to an expansion of focus in this regard to include other personality traits (Khan, 2019).…”
Section: Introductionmentioning
confidence: 96%
“…The results of research by Khan (2019) found that the attractiveness of the client's office environment can affect the level of professional skepticism. Therefore, understanding the factors that influence professional skepticism is the initial stage that can help auditors meet their expectations for performing tasks with a high level of professional skepticism.…”
Section: Introductionmentioning
confidence: 99%
“…Given the significance and associated challenges of PS to auditing, there have been calls for more studies to examine the determinants of auditor scepticism and how it can be enhanced (Carpenter & Reimers, 2013; Hurtt et al, 2013; Nelson, 2009; Nolder & Kadous, 2018). Many studies examine various situational and individual factors that influence auditors' PS (Carpenter & Reimers, 2013; Harding & Trotman, 2017; Khan & Harding, 2020; Kim & Trotman, 2015; Ying et al, 2020). Among these is the recognition that audit partners' preferences communicated to audit teams are important in influencing auditors' sceptical judgements.…”
Section: Introductionmentioning
confidence: 99%